Source of the aeolian sediments in the Yarlung Tsangpo valley and its potential dust contribution to adjacent oceans - Ling, Zhiyong; Yang, Shengli; Xia, Dunsheng; Wang, Xin; Chen, Fahu (Earth surface processes and landforms, 2022)
Surface sediments such as aeolian sand, loess/sandy loess, and fluvial/alluvial clastics are widespread in the Yarlung Tsangpo (YT) catchment and across the Tibetan Plateau (TP). However, it is debated whether the source of the aeolian sediments is local or remote, involving transport across large regions, and whether the surface sediments, especially aeolian deposits, are a major source of global dust. Here, we use strontium‐neodymium (Sr‐Nd) isotopic analysis and modern observations of dust emissions to investigate the provenance of aeolian sediments from the YT catchment and adjacent areas during different periods (modern, Holocene, Late Pleistocene), and the relationship between surface sediments of the TP and the dust component of sediments in the Japan Sea and the North Pacific Ocean. Strontium‐87/strontium‐86 (87Sr/86Sr) and neodymium isotopic ratio (εNd) show a wide range of variation in different areas (87Sr/86Sr varies from 0.707996 to 0.731078, and εNd from −6.2 to −13.6), influenced by the composition of the clastic material derived from the local parent rock; additionally, there are no significant variations between size fractions. Due to local recycling the aeolian sedimentary systems in the southern TP are supplied with clastic material from proximal sources, and they are unlikely to receive large quantities of long‐range dust transported from regions such as the Taklimakan desert in Central Asia. Dust emission occurs mainly in the dry season (from March to May) and the dust is carried on the upper‐level westerly jet stream and then deposited downwind in the Japan Sea and the North Pacific Ocean, thus contributing to global dust. Strontium‐neodymium (Sr‐Nd) isotopic signatures of the Tibetan Plateau (TP) surface sediments show wide regional variation related to local parent rock. Sediments on the southern TP are mainly sourced locally due to self‐circulation processes. Compared with the Taklimakan and northern China deserts, the TP is more likely to be the main dust source for the Japan Sea/North Pacific Ocean; dust emission in spring is carried into the upper‐level westerly jet and carried fat to the east, thus contributing to global dust.